2022
DOI: 10.1016/j.cegh.2021.100944
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic consumption and compliance to hospital antibiotic policy in the surgery, orthopedics and gynecology wards of a tertiary care hospital

Abstract: To evaluate antibiotic consumption and compliance to hospital antibiotic policy in the surgery, orthopedics and gynecology wards of a tertiary care hospital. Methods: A prospective observational study was conducted over eight months on adult inpatients prescribed with antibiotics. Data were collected using a predesigned antibiotic form and evaluated using Defined Daily Dose per 100 bed-days. Antibiotics prescribed were classified using World Health Organization Access, Watch and Reserve classification (WHO AWa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Literature has shown that prescribers which adhere to the AWaRe protocol have reported a reduction in AMR cases in their healthcare facilities [24] [25]. However, most prescribers do not adhere to the AWaRe protocol, thereby worsening the number of microorganisms developing resistance to antibiotics [26] [27]. Conversely, in Ghana, prescribers adhered to the AWaRe classification protocol, indicating good AMS [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature has shown that prescribers which adhere to the AWaRe protocol have reported a reduction in AMR cases in their healthcare facilities [24] [25]. However, most prescribers do not adhere to the AWaRe protocol, thereby worsening the number of microorganisms developing resistance to antibiotics [26] [27]. Conversely, in Ghana, prescribers adhered to the AWaRe classification protocol, indicating good AMS [28].…”
Section: Introductionmentioning
confidence: 99%
“…The AWaRe protocol also guides prescribers to ensure that they prescribe more than 60% of Access group antibiotics compared to the other groups [33]. However, evidence has shown an overprescribing of Watch group antibiotics compared to Access antibiotics [27] [30] [33] [34].…”
Section: Introductionmentioning
confidence: 99%
“…Hầu Tỷ lệ tuân thủ chung của nghiên cứu là 78,1%. Khi so sánh với nghiên cứu về việc sử dụng KSDP trong phẫu thuật chấn thương chỉnh hình khác, nghiên cứu của chúng tôi có tỷ lệ tuân thủ chung thấp hơn nghiên cứu của Thomas (2022) (86,3%) [8].…”
Section: Bàn Luậnunclassified
“…Literature has shown that prescribers that adhere to the AWaRe protocol have reported a reduction in AMR cases in their healthcare facilities [22,23]. However, most prescribers do not adhere to the AWaRe protocol, thereby worsening the number of microorganisms developing resistance to antibiotics [24,25]. Conversely, in Ghana, prescribers adhered to the AWaRe classi cation protocol, indicating good AMS [26].…”
Section: Introductionmentioning
confidence: 99%
“…The AWaRe protocol also guides prescribers to ensure they prescribe more than 60% of Access group antibiotics compared to the other groups [31]. However, evidence has shown an overprescribing of Watch group antibiotics compared to Access antibiotics [25,28,31,32].…”
Section: Introductionmentioning
confidence: 99%